A Textual Analysis of the Use of Sunna in Malik's Legal Doctrine - Kusmana Kusmana (Refleksi, 2000)
The sources of Malik's legal doctrine lie in texts, opinion and customary law. The textual sources of his doctrine consist of the paper will concentrate.